Integrasi Kebijakan Perpajakan dengan Kerangka Kerja ESG untuk Mencapai Sustainable Development - Sebastian Gerald Wesley Silalahi; Lorina Siregar Sudjiman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the integration of tax policy with the Environmental, Social, and Governance (ESG) framework in supporting the achievement of sustainable development. Current sustainability challenges require public policies that are not only focused on state revenue collection but also capable of encouraging more environmentally friendly, inclusive, and accountable economic behavior. As a fiscal instrument, taxation has strategic potential to promote business activities aligned with ESG principles through incentives, disincentives, and strengthened policy governance. This study uses a qualitative approach with a literature review method to examine the relationship between tax policy, ESG, and sustainable development. The findings indicate that integrating tax policy with ESG can serve as an important instrument in supporting the transition toward a green economy, strengthening social responsibility, and improving transparency and accountability in fiscal policy. However, its implementation still faces challenges such as suboptimal policy harmonization, limited measurement indicators, and weak cross-sector integration. Therefore, a more comprehensive tax policy design is needed to make a tangible contribution to sustainable development.